POET(H)IC INQUIRY AND THE FICTIVE IMAGINATION: SILENCE, VOICE AND STORY - Duff, Heather (Art/Research International)

(untitled) (University of Alberta, 2021)
Women’s voices have historically been silenced in a vast array of contexts. Ethical incongruities exist between theoretical perspectives regarding right action for protection of women’s dignity and the tangible dilemma presented by systemic silencing. A fictive imagination found in the arts – and literature in particular – often plays a role in bridging that ethical gap between theory and practice. Using my arts-based approach of poet(h)ic inquiry (Duff, 2016a), I portray the symbolic power of women’s voices, fictionality, and textual polyvocality in a research-based play. Poet(h)ic inquiry is a method for ethical reflection incorporating spiritual and poetic-aesthetic values: a pedagogical space of inquiry within a non-fixed site of teaching, life-long learning, creativity, and knowing, located at the confluence of the creative writing process (in the context of fiction as research), ethics, and spirit. In “Story about Story. Toronto 2001,” I inquire poet(h)ically, in a speculative fictional tale about a woman’s journey with her baby, using research journal data and “freefall writing” notes as springboard for a “fictive leap” (Mitchell, 1977). Through the fictive writing process, knowledge is generated with respect to themes of isolation and connection towards re-finding the lost self’s language. Voices heard and unheard, pinpoint an ethic of meaning towards transcending silence, suffering, and colonial injustices. My story evokes ironies and eco-ethical queries within wildlife research, as well as questions evoked by the sensory overload of urban commerce, and an unspoken class system. I include reflections on fictionality, literature, and redemption.